Synthesis, structure, and thermal stability of poly(methyl methacrylate)-co- poly(3-tri(methoxysilyil)propyl methacrylate)/ montmorillonite nanocomposites - Carvalho, Hudson W.P. [UNESP]; Suzana, Ana F. [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Wiley, 2013)
The structure and the thermodegradation behavior of both poly(methyl methacrylate)-co-poly(3-tri(methoxysilyil)propyl methacrylate) polymer modified with silyl groups and of intercalated poly(methyl methacrylate)-co-poly(3- tri(methoxysilyil)propyl methacrylate)/Cloisite 15A™ nanocomposite have been in situ probed. The structural feature were comparatively studied by Fourier transform infrared spectroscopy (FTIR), 13C and 29Si nuclear magnetic resonance (NMR), and small angle X-ray scattering (SAXS) measurements. The intercalation of polymer in the interlayer galleries was evidenced by the increment of the basal distance from 31 to 45 Å. The variation of this interlayer distance as function of temperature was followed by in situ SAXS. Pristine polymer decomposition pathway depends on the atmosphere, presenting two steps under air and three under N2. The nanocomposites are more stable than polymer, and this thermal improvement is proportional to the clay loading. The experimental results indicate that clay nanoparticles play several different roles in polymer stabilization, among them, diffusion barrier, charring, and suppression of degradation steps by chemical reactions between polymer and clay. Charring is atmosphere dependent, occurring more pronounced under air. © 2012 Society of Plastics Engineers.
Keywords: Interlayer distance; Montmorillonite nanocomposites; Nuclear magnetic resonance(NMR); Polymer stabilization; Propyl methacrylate; Small angle X-ray scattering; Structural feature; Thermo-degradation; Degradation; Esters; Fourier transform infrared spectroscopy; Nanocomposites; Polymers